Type 2 diabetes mellitus as a possible risk factor for myasthenia gravis: a case–control study - Liu, Yu-Dong; Tang, Fang; Li, Xiao-Li; Liu, Ya-Fei; Zhang, Peng; Yang, Chun-Lin; Du, Tong; Li, Heng; Wang, Cong-Cong; Liu, Ying; Yang, Bing; Duan, Rui-Sheng (Frontiers in Neurology, 2023)
Background A certain number of myasthenia gravis (MG) patients clinically had type 2 diabetes mellitus (T2DM) prior to MG onset, which suggests that the onset of MG may correlate with the history of T2DM. This study aimed to examine the correlation between MG and T2DM. Methods In a single-center, retrospective, 1:5 matched case–control study, all 118 hospitalized patients with a diagnosis of MG from 8 August 2014 to 22 January 2019 were enrolled. In total, four datasets with different sources of the control group were retrieved from the electronic medical records (EMRs). Data were collected at the individual level. A conditional logistic regression analysis was used to test the risk of MG associated with T2DM. Findings The risk of MG was significantly associated with T2DM, and there were notable differences by sex and age. Whether compared to the general population, general hospitalized patients without autoimmune diseases (AIDs), or patients with other AIDs except MG, women aged over 50 years with T2DM had an increased risk of MG. The mean onset age of diabetic MG patients was more than that of the non-diabetic MG patients. Interpretation This study demonstrates that T2DM is strongly associated with the subsequent risk of MG and varies significantly by sex and age. It reveals that diabetic MG may be a unique subtype that is different from the conventional MG subgroup classification. More clinical and immunological features of diabetic MG patients need to be explored in further studies.